Reasons Why Female Students Do Not Start a Business? A Brief Analysis - Margareta Ilie; Constantin Ilie (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2024)
As old as the world, the low number of businesses run by women is still a subject that raises many discussions and research. The present work is a short study of how women still in the period of higher education look at the financial risks involved in financing and supporting the business. Using the method of graphic representation and visualization of data evolution for analysis, the authors aim to determine the relationship of influence between the importance of these risks and women's intention to start a business. The data were recorded following the application of a survey between February-March 2023 on a sample of 264 women. Differences were determined between how financial risks are viewed by urban and rural women, and by married versus unmarried women. A conclusion is that urban women consider education a must, while for rural women it is not a necessity in running a business.